Global Summit on Student Affairs and Services (Journal of Student Affairs in Africa, 2021)
In the most recent issue of the Journal of Student Affairs in Africa (JSAA), readers were introduced to the 3rd Global Summit on Student Affairs and Services that was hosted by Stellenbosch University (SU) in Cape Town, South Africa, this past October 2016.This summary will provide a more detailed outline of the organisation of the summit, its processes, and the final written product for the 2016 summit, which was initiated by theInternational Association for Student Affairs and Services (IASAS) and Student Affairs Administrators in Higher Education (NASPA).The first Global Summit in 2012 was held in Washington, D.C., which is the home office of NASPA and in 2014 the summit was held in Rome, Italy and was hosted by the European University College Association (EuCA). Perozzi, Giovanucci and Shea (2016), note that the summit “is not a ‘conference’ in the traditional sense; rather, the methodology allows for emergent issues and a discussion of concepts that are most relevant to participants” (p. 24). Following the same ideals, forty participants, from 19 different countries, who support students on college and university campuses around the world, were invited to South Africa for a rich dialogue around critical issues facing student affairs and services. Some of the issues that surfaced in 2012 and 2014 were used as a basis for further reflection in the 3rd summit. These themes included professionalisation and internationalisation of the field, employability and soft skills, engaging in student activism, and access and inclusion.